Hsp70 protein levels and thermotolerance in Drosophila subobscura: a reassessment of the thermal co-adaptation hypothesis. - Calabria, G. (2013)
Copyright © 2012 The Authors. Journal of Evolutionary Biology © 2012 European Society For Evolutionary Biology.